Grewia spp. Biopolymer as Low-Cost Biosorbent for Hexavalent Chromium Removal - G. P. Kofa; G. R. Nkoue Ndongo; M. B. Kameni Ngounou; M. N. Nsoe; E. V. Amba; S. Ndi Koungou (Journal of Chemistry)
In this study, Grewia spp. biopolymer was utilized as a biosorbent for elimination of hexavalent chromium from water. Fourier-transform infrared spectrometry (FTIR) and X-ray diffraction (XRD) were performed for characterization of the biosorbent. Experiments were conducted in a batch mode at room temperature (25 ± 2°C) and agitation speed of 100 rpm to determine the influence of biosorbent dose, contact time, Cr(VI) concentration, and initial solution pH. It was found that equilibrium was attained in 50 min. A pseudo-first-order model suited well than a pseudo-second-order model. Biosorption capacity of Grewia spp. biopolymer increased with increase in concentration and depended on the solution pH. Langmuir and Freundlich models described experimental data very well. These findings showed that Grewia spp. biopolymer can serve as a biosorbent for elimination of Cr(VI) from water.